Agency and Structural Dynamics in Islamic Organization-Based Higher Education: A Comparative Analysis - Mustajab; Ach. Barocky Zaimina (Institut Agama Islam An-Nawawi Purworejo, 2025)
This study aims to explore the dynamics of agency and structure within Islamic-based higher education institutions through a comparative approach at Universitas Muhammadiyah Jember (Unmuh) and Universitas Islam Jember (UIJ). The research is driven by the need to understand how universities rooted in Islamic values navigate the tension between preserving ideological identity and responding to the demands of globalization. A qualitative method was employed, with data collected through in-depth interviews, document analysis, and participatory observation. The findings reveal that Unmuh tends to emphasize internal agency to maintain ideological autonomy based on Muhammadiyah values, while UIJ is more open to external collaboration to enhance global relevance and competitiveness. Both institutions utilize organizational structures as instruments to instill values, shape norms, and foster adaptation through formal policies, human resource development, and digital transformation. The discussion is enriched through a theoretical dialogue involving Giddens' structuration theory, Archer's morphogenetic approach, and the Islamic educational ethics of Halstead and Al-Attas. The novelty of this research lies in its simultaneous exploration of agency and structure in a comparative manner, and in the integration of Islamic values into leadership, policymaking, and institutional transformation within the context of contemporary Islamic higher education.